Trunk Impairment as a Predictor of Activities of Daily Living in Acute Stroke - Ishiwatari, Masahiro; Honaga, Kaoru; Tanuma, Akira; Takakura, Tomokazu; Hatori, Kozo; Kurosu, Akihiro; Fujiwara, Toshiyuki (Frontiers in Neurology, 2021)
Background and purpose: Trunk function plays a key role in performing activities of daily living (ADL) including locomotion and sitting. Sitting and ADL should be performed as early as possible especially during the acute phase of stroke rehabilitation. Therefore, this study aimed to assess trunk function among patients with acute stroke using the Trunk Impairment Scale (TIS) and to predict its functional outcomes. Methods: Overall, 67 patients with acute stroke (i.e., within 2 days of occurrence of the stroke) were included. The following clinical assessment items were obtained within 48 h after stroke onset and on the day before discharge from the hospital. Trunk function was examined using TIS and Trunk Control Test (TCT). The motor function of the upper and lower extremities was assessed using the stroke impairment assessment set motor (SIAS-M) score, and ADL was assessed using functional independence measure motor (FIM-M) items. Results: Multiple regression analysis was performed using the stepwise regression method, using the total FIM-M score following discharge as the dependent variable and age, TIS, TCT, SIAS-M, and FIM-M within 48 h after stroke onset as the independent variables. Age, TIS, and FIM-M within 48 h after stroke onset were selected as the input variables and showed a high-adjusted determination coefficient (R2 = 0.79; P < 0.001). Conclusion: TIS is a reliable method for evaluating trunk control function and is an early predictor of ADL among patients with acute stroke.